Regional Potential-Based Strategies to Enhance Vocational Education Effectiveness in SMK Development on the East Coast of Aceh - M, Syukurdi; ., Badaruddin; Lubis, Suwardi; ., Charloq (Journal of Ecohumanism, 2025)
Vocational high schools (SMKs) are essential in enhancing human resource quality by aligning education with regional potential. However, on the East Coast of Aceh, graduates frequently face long waiting periods for employment due to local industries' preference for external recruits. This study examines the potential for SMK development based on regional potential and identifies priority strategies to improve their effectiveness. Simple linear regression was used to evaluate the relationship between SMK graduate outcomes and competency alignment with market demands, while the Analytical Hierarchy Process (AHP) determined key priorities, focusing on leadership (weight: 0.421) and school governance improvement (weight: 0.397). The findings reveal that 81% and 82% of graduates work within their expertise locally and outside Aceh, respectively, while 87.3% and 88.85% work outside their fields in Aceh and beyond. Moreover, 85.4% pursue higher education or formal service, 32% engage in entrepreneurship, and 45.1% remain unemployed. These outcomes indicate a need for improved alignment between education and local industry demands. Recommended strategies include curriculum adjustments to incorporate local economic sectors such as agribusiness, fisheries, and tourism, strengthening collaborations between SMKs and industries, and enhancing local government support. This study underscores the importance of sustainable, regionally relevant SMK development to improve graduate employability and competitiveness in both local and national labor markets.